Variations in mitochondrial cytochrome b region among Ethiopian indigenous cattle populations assert Bos taurus maternal origin and historical dynamics - Tarekegn, G.M.; Xiao-yang Ji; Xue Bai; Bin Liu; Wenguang Zhang; Birungi, Josephine; Djikeng, Appolinaire; Tesfaye, K. (Asian-Australasian Association of Animal Production Societies, 2018)
Objective This study was carried out to assess the haplotype diversity and population dynamics in cattle populations of Ethiopia. Methods We sequenced the complete mitochondrial cytochrome b gene of 76 animals from five indigenous and one Holstein Friesianà Barka cross bred cattle populations. Results In the sequence analysis, 18 haplotypes were generated from 18 segregating sites and the average haplotype and nucleotide diversities were 0.7540±0.043 and 0.0010±0.000, respectively. The population differentiation analysis shows a weak population structure (4.55%) among the populations studied. Majority of the variation (95.45%) is observed by within populations. The overall average pair-wise distance (F ST) was 0.049539 with the highest (F ST = 0.1245) and the lowest (F ST = 0.011) F ST distances observed between Boran and Abigar, and Sheko and Abigar from the indigenous cattle, respectively. The phylogenetic network analysis revealed that all the haplotypes detected clustered together with the Bos taurus cattle and converged to a haplogroup. No haplotype in Ethiopian cattle was observed clustered with the reference Bos indicus group. The mismatch distribution analysis indicates a single population expansion event among the cattle populations. Conclusion Overall, high haplotype variability was observed among Ethiopian cattle populations and they share a common ancestor with Bos taurus.